Checklist of the family Pipunculidae (Diptera) of Finland - Kehlmaier, Christian (Pensoft Publishers, 2014)
Abstract. A checklist of the Pipunculidae (Diptera) cited from Finland is presented. At present, 107 species have been recorded.